Electromagnetic Functions Modulation of Recycled By-Products by Heterodimensional Structure - Nan, Ze; Wei, Wei; Lin, Zhenhua; Yuan, Ruimei; Zhang, Miao; Zhang, Jincheng; Ouyang, Jianyong; Chang, Jingjing; Li, Hejun; Hao, Yue (Nano-Micro Letters, 2025)
One of the significant technological challenges in safeguarding electronic devices pertains to the modulation of electromagnetic (EM) wave jamming and the recycling of defensive shields. The synergistic effect of heterodimensional materials can effectively enable the manipulation of EM waves by altering the nanostructure. Here we propose a novel approach for upcycling by-products of silver nanowires that can fabricate shape-tunable aerogels which enable the modulation of its interaction with microwaves by heterodimensional structure of by-products. By-product heterodimensionality was used to design EM-wave-jamming-dissipation structures and therefore two typical tunable aerogel forms were studied. The first tunable form was aerogel film, which shielded EM interference (EMI shielding effectiveness (EMI SE) > 89 dB) and the second tunable form was foam, which performed dual EM functions (SE > 30 dB& reflective loss (RL) < -35 dB, effective absorption bandwidth (EAB) > 6.7 GHz). We show that secondary recycled aerogels retain nearly all of their EM protection properties, making this type of closed-loop cycle an appealing option. Our findings pave the way for the development of adaptive EM functions with nanoscale regulation in a green and closed-loop cycle, and they shed light on the fundamental understanding of microwave interactions with heterodimensional structures. Highlights: 1 Turning trash into treasure: The outstanding tunable aerogels were fabricated via heterodimensional by-products of silver nanowires. The first tunable form, aerogel film, shields electromagnetic interference (EMI SE > 89 dB), while the second tunable form, aerogel foam, performs dual EM functions (EMI SE > 30 dB and RL < -35 dB, EAB > 6.7 GHz). 2 Recycle again: The secondary recycled aerogels retain nearly all of their EM protection qualities, making this closed-loop cycle desirable.